Foreign acquisitions, domestic multinationals, and R&D - Roger Bandick; Holger Görg; Patrik Karpaty (Centre for Economic Policy Research (CEPR), 2010)
The aim of this paper is to evaluate the causal effect of foreign acquisition on R&D intensity in targeted domestic firms. We are able to distinguish domestic multinationals and non-multinationals, which allows us to investigate the fear that the change in ownership of domestic to foreign multinationals leads to a reduction in R&D activity in the country, as headquarter activities are relocated to the new owner's home country. We use unique and rich firm level data for the Swedish manufacturing sector and different micro-econometric estimation strategies in order to control for the potential endogeneity of the acquisition dummy. Overall, our results give no support to the fears that foreign acquisition of domestic firms lead to a brain drain of R&D activity in Swedish MNEs. Rather, this paper finds robust evidence that foreign acquisitions lead to increasing R&D intensity in acquired domestic MNEs and non-MNEs.
Keywords: F23; 330; domestic multinationals; foreign acquisition; R&D; Multinationales Unternehmen; Direktinvestition; Übernahme; Industrielle Forschung; Brain Drain; Schätzung; Schweden